Peripheral contributions to the development and maintenance of inflammation and pain in arthritis - Amanitis, Dimitrios (2022)
Vascular endothelial growth factor A (VEGF-A) is a key regulator of vascular growth, permeability, and neuronal function. During articular inflammation in osteoarthritis (OA) and rheumatoid arthritis (RA), there is increased synovial angiogenesis and upregulation of angiogenic growth factors such as VEGF-A. VEGF-A comprises of two splice variant families, VEGF-Axxxa and VEGF-Axxxb (xxx represents the number of amino acids, from 121 to 206), resulting from alternative splice site selection in exon 8. Distal site selection and VEGF-Axxxa expression is controlled by Serine/Arginine Rich Splicing Factor Kinase 1 (SRPK1), which phosphorylates Serine/Arginine Rich Splicing Factor 1 (SRSF1), inducing its translocation to the nucleus. In most normal tissues, VEGF-Axxxb isoforms predominate, with anti-nociceptive and anti-angiogenic functions. In contrast, in pathological conditions such as inflammation and solid tumours SRPK1/SRSF1 activation causes VEGF-Axxxa isoforms to predominate, exerting pro-nociceptive and pro-angiogenic actions. VEGF-A has been proposed as a therapeutic target in OA. To date, a relation between VEGF-A and pain in OA has been reported, but there are no published data on the functionally distinct VEGF-A splice variants inflammation and pain in human OA and RA.